2020
DOI: 10.1158/0008-5472.can-19-2348
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-Induced Senescence Drives Bone Loss

Abstract: Chemotherapy is important for cancer treatment, however, toxicities limit its use. While great strides have been made to ameliorate the acute toxicities induced by chemotherapy, long-term comorbidities including bone loss remain a significant problem. Chemotherapy-driven estrogen loss is postulated to drive bone loss, but significant data suggests the existence of an estrogen-independent mechanism of bone loss. Using clinically relevant mouse models, we showed that senescence and its senescence-associated secr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 56 publications
8
67
1
Order By: Relevance
“…In this context, Sheila Stewart discussed her findings related to the impact of senescence in chemotherapy-induced bone loss, a common comorbidity in cancer patients. Using a genetic mouse model, her team found that elimination of senescent cells that arise after chemotherapy prevented bone loss [58]. In addition, targeting SASP pathways using pharmacological inhibition of p38MAPK/MK2 signaling also limited chemotherapy-induced side effects [58].…”
Section: Prognostic and Therapeutic Implications Of Microenvironmentamentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Sheila Stewart discussed her findings related to the impact of senescence in chemotherapy-induced bone loss, a common comorbidity in cancer patients. Using a genetic mouse model, her team found that elimination of senescent cells that arise after chemotherapy prevented bone loss [58]. In addition, targeting SASP pathways using pharmacological inhibition of p38MAPK/MK2 signaling also limited chemotherapy-induced side effects [58].…”
Section: Prognostic and Therapeutic Implications Of Microenvironmentamentioning
confidence: 99%
“…Using a genetic mouse model, her team found that elimination of senescent cells that arise after chemotherapy prevented bone loss [58]. In addition, targeting SASP pathways using pharmacological inhibition of p38MAPK/MK2 signaling also limited chemotherapy-induced side effects [58]. Senescence is not only triggered by chemotherapy but occurs normally in healthy individuals, as part of the aging process, and may directly impact tumorigenesis.…”
Section: Prognostic and Therapeutic Implications Of Microenvironmentamentioning
confidence: 99%
“…However, studies based on therapy-induced senescence (TIS) indicated the emergence of adverse effects on cancer treatment (95,96). Chemotherapy-induced SASP drives bone loss in breast cancer and its regulation by p38-MAPK-MK2 inhibition could preserve bone, improving the quality of life of patients (97). TIS may contribute to unwanted outcomes through the stimulation of inflammation by increased secretion of SASP factors, the induction of senescence-associated stemness phenotype or senescence cell scape and further proliferation recovery (98-100).…”
Section: The Dual Interface Of Autophagy and Senescencementioning
confidence: 99%
“…For example, limiting therapy-induced SASPs by inhibiting the p38 MAPK-MK2 pathway could rescue chemotherapy-induced bone loss in doxorubicin-treated mouse models. 17 Wang et al found that TIS cells became vulnerable to apoptosis induction by ABT263 in vitro, and demonstrated the feasibility of the sequential therapy for cancer in which senotherapy could be administered concomitantly or after senescence-inducing treatment. 25 In preclinical mouse models of ovarian and breast cancer, concurrent PARPi and ABT263 treatment was observed to have a significant potentiation of cell killing.…”
Section: Targeting Senescence Cancer Cellsmentioning
confidence: 99%